THE IMPACT OF INTERNAL WHITISH AND REFLECTIVE GRAINING ON THE CLARITY GRADING OF D-TO-Z COLOR DIAMONDS AT THE GIA LABORATORY - King J.M.; Moses T.M.; Wang W. (My University, 2006)
Unlike many other characteristics that affect the clarity grade of a diamond, determination of the impact of "whitish" graining and "reflective" graining requires analysis that goes beyond visibility at 10× magnification. The importance of this determination is further underscored by the fact that such graining often is the only characteristic present in large, high-clarity, high-color diamonds. This article reviews the history of reporting on such graining by the GIA Laboratory, considers the causes of the different types of graining most commonly encountered, and examines the methodology and critical assessment GIA graders use to determine the impact of such graining on the clarity grade of a diamond.